2010
DOI: 10.1161/circinterventions.110.955310
|View full text |Cite
|
Sign up to set email alerts
|

Mehran Contrast-Induced Nephropathy Risk Score Predicts Short- and Long-Term Clinical Outcomes in Patients With ST-Elevation–Myocardial Infarction

Abstract: Background-The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
93
1
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(102 citation statements)
references
References 39 publications
6
93
1
2
Order By: Relevance
“…The reported incidence of AKI is 1% to 3% in patients undergoing elective PCI17, 19, 20, 21 but rises significantly to 10% to 16% in patients undergoing pPCI 3, 22, 23. The large increase in incident AKI is the result of heart failure, hemodynamic instability, and pharmacological interventions associated with STEMI rather than the use of greater contrast volume.…”
Section: Discussionmentioning
confidence: 99%
“…The reported incidence of AKI is 1% to 3% in patients undergoing elective PCI17, 19, 20, 21 but rises significantly to 10% to 16% in patients undergoing pPCI 3, 22, 23. The large increase in incident AKI is the result of heart failure, hemodynamic instability, and pharmacological interventions associated with STEMI rather than the use of greater contrast volume.…”
Section: Discussionmentioning
confidence: 99%
“…This score, when proposed, was observed to have a c-statistic of 0.67 but excluded patients treated with PPCI and patients in shock [8] However, the Mehran risk score was later tested for patients with STEMI who underwent primary PCI and showed a strong predictive value for CIN (c-statistic: 0.80 to 0.84) [9]. Ando et al, demonstrated that the ACEF risk score which include Age, serum crat is useful to predict CIN in patients with STEMI, while also demonstrating that the modified ACEF (AGEF) score has a similar discriminative ability for CIN [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…10 However, this is not the case for patients with known reduced renal function or renal risk factors where a permanent reduction in renal function and a poorer prognosis may be the consequence. 11 To avoid these serious side effects of contrast administration, 2 precautions in general are recommended, namely to reduce the dose of contrast media as much as possible 3 and to ensure optimal hydration before and immediately after the procedure by administration of intravenous sodium chloride. 12 In addition to these general recommendations, several more specific pharmacological interventions have been proposed for the protection of renal function.…”
mentioning
confidence: 99%
“…15,16 Patients treated for STEMI with primary PCI are most often exposed for contrast media without preexisting knowledge of renal function, and the patients are in different conditions of hydration. Only a few studies 7,11,17 have investigated this problem in different settings. To investigate the degree of renal impairment and the possible preventive effect of NAC and intravenous NaHCO 3 , alone or in combination, we initiated the present randomized and prospective study.…”
mentioning
confidence: 99%